2012
DOI: 10.5380/avs.v18i1.29393
|View full text |Cite
|
Sign up to set email alerts
|

Eficácia Do Fosfato De Levamisol Em Nematódeos Gastrintestinais De Caprinos E Ovinos

Abstract: RESUMO:O parasitismo gastrintestinal é considerado o principal entrave na produção de pequenos ruminantes e a ocorrência de parasitos resistentes aos anti-helmínticos tem dificultado seu controle. O objetivo deste trabalho foi avaliar a sensibilidade de nematóides gastrintestinais ao levamisol, em rebanho ovino e caprino criados simultaneamente. Foram utilizados 28 caprinos da raça Bôer e 28 ovinos da raça Texel, naturalmente infectados. Ambas as espécies foram divididas em quatro grupos de sete animais: T1) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
1
1
0
6
Order By: Relevance
“…The efficacy of levamisole is consistent with those described by Sprenger et al (2013), who reported the effectiveness of this active ingredient in doses of 9.00 and 6.75mg/kg administered to sheep on a farm in the municipality of Balsa Nova, state of Paraná, Brazil. On the other hand, several authors have reported the ineffectiveness of this drug in flocks of sheep in Brazil.…”
Section: Resultssupporting
confidence: 78%
“…The efficacy of levamisole is consistent with those described by Sprenger et al (2013), who reported the effectiveness of this active ingredient in doses of 9.00 and 6.75mg/kg administered to sheep on a farm in the municipality of Balsa Nova, state of Paraná, Brazil. On the other hand, several authors have reported the ineffectiveness of this drug in flocks of sheep in Brazil.…”
Section: Resultssupporting
confidence: 78%
“…Levamisole, albeit a long-standing drug with reports of resistance around the world and in Brazil dating back to the 70s (LE JAMBRE et al, 1976;SANTIAGO et al, 1977), is reportedly the anthelmintic that has shown the highest effectiveness over the years in Brazil, including in recent surveys. In Brazil, its reported effectiveness rate was higher than that of other drugs tested in eight studies involving sheep (AMARANTE et al, 1992;THOMAZ-SOCCOL et al, 1996;MELO et al, 2003;ROSALINSKI-MORAES et al, 2007;CRUZ et al, 2010;VERÍSSIMO et al, 2012;SPRENGER et al, 2013) and in three studies involving goats (MATTOS et al, 2000;RODRIGUES et al, 2007;LIMA et al, 2010a). Levamisole has also been reported to be more effective than other antiparasitics in Canada (FALZON et al, 2013), Denmark (PENA-ESPINOZA et al, 2014) and Australia (LYNDAL-MURPHY et al, 2014).…”
Section: Developments In Research and The Effectiveness Of Anthelmintmentioning
confidence: 99%
“…Valores superiores ao aceitável para o tratamento da parasitose gastrintestinal que deveria ser igual ou inferior a 500 (Krzyzaniak, 2003, Cringoli et al, 2004, Sprenger et al, 2012.…”
Section: Resultsunclassified
“…é o único parasito que está associado ao grau da coloração da conjuntiva ocular, devido ao grau de anemia, característica relacionada ao seu hábito hematófago e pode ser diagnosticado através do método FAMACHA ® (Domingues et al, 2013, Sprenger et al, 2012. Segundo Chagas et al (2007) No presente estudo, após a realização do método FAMACHA ® , verificou-se valores médios para primavera e verão de 1,80 e 2,83, respectivamente.…”
Section: Resultsunclassified